Lenses on reading an introduction to theories and models - Tracey, Diane H.; Morrow, Lesley Mandel (New York Guilford Press, 2006)
Provides a survey of the major theories and models that influence reading instruction and research. This book helps readers learn why theory matters in designing and implementing high-quality instruction; and how to critically evaluate the assumptions and beliefs that guide their own work with students. It is useful for graduate students.
Introduction to theories and models -- Early roots : early theories and models applicable to reading (400 B.C.-1899) -- Behaviorism : the dominant educational theory for 50 years (1900-1950s) -- Constructivism (1920s-present) -- Theories of literacy development (1930s-present) -- Social learning perspectives (1960s-present) -- Information/cognitive processing perspectives (1950s-1970s) -- Information/cognitive processing perspectives, continued (1980s) -- Information/cognitive processing perspectives : state of the art (1989-present) -- Putting it all together.
Photocopy.
Keywords: Reading philosophy -- History; Reading -- Research -- Methodology -- History; Reading, Psychology of -- History